A Search for Molecules at Low Frequency with the Murchison Widefield Array - Tremblay, Chenoa (Curtin University, 2018)
I used a wide-field, low-frequency telescope to search for signals from molecules, atoms, and exo-planets, surveying the Galactic Centre and Orion to detect molecules for the first time below 700MHz. In collaboration, I used the same data to set upper limits on the signal strength of extraterrestrial civilisations. Utilising surveys at infrared and radio wavelengths, I found evidence that high-mass stars can form in isolation.